Mucosal Inflammatory Response to Salmonella typhimurium Infection - Patel, Samir; McCormick, Beth A. (Frontiers in Immunology, 2014)
The human intestinal epithelium consists of a single layer of epithelial cells that forms a barrier against food antigens and the resident microbiota within the lumen. This delicately balanced organ functions in a highly sophisticated manner to uphold the fidelity of the intestinal epithelium and to eliminate pathogenic microorganisms. On the luminal side, this barrier is fortified by a thick mucus layer, and on the serosal side exists the lamina propria containing a resident population of immune cells. Pathogens that are able to breach this barrier disrupt the healthy epithelial lining by interfering with the regulatory mechanisms that govern the normal balance of intestinal architecture and function. This disruption results in a coordinated innate immune response deployed to eliminate the intruder that includes the release of antimicrobial peptides, activation of pattern-recognition receptors, and recruitment of a variety of immune cells. In the case of Salmonella enterica serovar typhimurium (S. typhimurium) infection, induction of an inflammatory response has been linked to its virulence mechanism, the type III secretion system (T3SS). The T3SS secretes protein effectors that exploit the host’s cell biology to facilitate bacterial entry and intracellular survival, and to modulate the host immune response. As the role of the intestinal epithelium in initiating an immune response has been increasingly realized, this review will highlight recent research that details progress made in understanding mechanisms underlying the mucosal inflammatory response to Salmonella infection, and how such inflammatory responses impact pathogenic fitness of this organism.